Upaya Lembaga Penyiaran Publik (LPP) RRI Padang untuk Meningkatkan Kesadaran Masyarakat Melalui Pemanfaatan Media Sosial - Wati, Erna; Fitri, Nur Asyah Adelia; Syafril, Rizki (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
Radio is a mass communication medium that is closely related to the needs of society and can provide various information, entertainment, education, etc. The presence of the Internet has changed people's behavior patterns and RRI Padang has begun to trace developments in digital technology. RRI Padang strives to improve the quality of its broadcast programs, especially to stimulate public interest in social media. Background The aim of this research is to describe RRI Padang's efforts to increase public awareness through social media. This research is described using a qualitative approach using primary and secondary data. Interviews, observation, and documentation were used as data collection methods in this research. The data analysis technique used in this research is descriptive analysis using reduction, representation and inferential techniques. The results of this research are RRI Padang's efforts to increase public awareness through social media